2016
DOI: 10.1002/adhm.201500815
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Neurite Contact Guidance in Ubiquitin Ligase E3a (Ube3a)‐Deficient Hippocampal Neurons on Nanostructured Substrates

Abstract: Recent discoveries indicate that during neuronal development the signaling processes that regulate extracellular sensing (e.g., adhesion, cytoskeletal dynamics) are important targets for ubiquitination-dependent regulation, in particular through E3 ubiquitin ligases. Among these, Ubiquitin E3a ligase (UBE3A) has a key role in brain functioning, but its function and how its deficiency results in the neurodevelopmental disorder Angelman syndrome is still unclear. Here, the role of UBE3A is investigated in neurit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 82 publications
1
26
0
Order By: Relevance
“…Moreover, an overall excitatory network, due to a more severe decrease in inhibitory than excitatory inputs [197], possibly contributes to the increased seizure susceptibility observed in AS patients. In vitro studies using Ube3a knockdown or Ube3a KO neurons from mice have also shown that Ube3a loss of function decreased dendrite arborization, disrupted dendrite polarity and reduced apical dendrite length [198,199]. In addition, disrupted synaptic plasticity in the form of impaired LTP in different brain areas [45,193,200] and enhanced hippocampal mGluR-LTD [201] were also observed in AS mice (Table 1).…”
Section: Mtorc1 Signaling Pathway In Monogenic Autism Spectrum Dismentioning
confidence: 99%
“…Moreover, an overall excitatory network, due to a more severe decrease in inhibitory than excitatory inputs [197], possibly contributes to the increased seizure susceptibility observed in AS patients. In vitro studies using Ube3a knockdown or Ube3a KO neurons from mice have also shown that Ube3a loss of function decreased dendrite arborization, disrupted dendrite polarity and reduced apical dendrite length [198,199]. In addition, disrupted synaptic plasticity in the form of impaired LTP in different brain areas [45,193,200] and enhanced hippocampal mGluR-LTD [201] were also observed in AS mice (Table 1).…”
Section: Mtorc1 Signaling Pathway In Monogenic Autism Spectrum Dismentioning
confidence: 99%
“…Because we know that neurite growth is usually favored along NGs (i.e. aligned neurites are longer than misaligned ones) 55 , we quantitatively examined the spatial development of neurite arborization and we calculated the total length of the neurites aligned (alignment angle 0-15°) or perpendicular (alignment angle 75°-90°) to NG pattern on each substrate (reported in % over the total network length analyzed) (Fig. 8b).…”
Section: Scientific Reports |mentioning
confidence: 99%
“…Cell lysates (10 µg/line) were processed by immunoblot, as in 55 . Briefly, samples were resolved by gel electrophoresis (SDS-PAGE) using Gel Criterion XT-Precasted polyacrylamide gel 4-12% Bis-Tris (Biorad), transferred to nitrocellulose membranes by Trans-Blot Turbo transfer system (Biorad) and probed overnight at 4 °C with primary antibodies.…”
Section: Focal Adhesion Experiments and Live Cell Total Internal Reflmentioning
confidence: 99%
See 2 more Smart Citations